Electrospun bimetallic Au–Pt/TiO2/BaFe12O19 nanofibers as promising photocatalysts driven by visible light: Synthesis and characterization - Fatemeh Sadat Razavi; Davood Ghanbari; Elmuez A. Dawi; Masoud Salavati-Niasari (Journal of Science: Advanced Materials and Devices, 2023)
Photocatalysis is considered to be one of the most promising strategies for reducing water pollution, a global issue that threatens the environment. The electro-spinning technique was used to synthesize Pt–Au/TiO2/BaFe12O19 nanofibers. The optical part of a Pt–Au/TiO2 nanocomposite was obtained by surface plasmon resonance (SPR), and the magnetic part was obtained by using BaFe12O19 nanoparticles synthesized through ultrasound waves and Ficus carica extracts. Fourier Transform Infrared spectroscopy (FT-IR), X-Ray Powder Diffraction (XRD), Dispersive Spectra analysis (EDS), Scanning Electron Microscope (SEM), high-resolution Transmission Electron Microscopy (HR-TEM), Brunauer–Emmett–Teller (BET), Vibrating Sample Magnetometer (VSM) and diffuse reflectance spectroscopy (DRS) have been employed to assess products. The photocatalytic performance of Pt/TiO2, Au/TiO2, nanocomposites and Pt–Au/TiO2 BaFe12O19 nanofibers was investigated under visible light. In the presence of changing parameters, such as dye type (azo dyes with different numbers of azo groups), concentration and pH, the highest decolorization has been achieved 95.2%, with the reaction rate coefficient of 0.0247 min−1 for Acid Red 14 by Pt–Au/TiO2 nanofibers. The results of this study clearly demonstrate that noble metals may increase dye degradation through the electron sink effect of Pt and the SPR effect of Au.